Gaya Kognitif Field-Dependent dan Field-Independent sebagai Jendela Profil Pemecahan Masalah Polya dari Siswa SMP - Wulan, Eka Resti; Anggraini, Rusmala Eva (Journal Focus Action of Research Mathematic (Factor M), 2019)
The aim of this research is to describe junior high school students’ problem solving profile in the Pythagoras Theorem problem based on the cognitive styles of FI and FD. The results of this study is the FI subject is better than the FD subject. The FI subject understand the problem very well, arranging a solution plan well, implementing a plan properly, and looking back well. Different from previous research, subject FI make error even though not any Polya’s step. Nevertheless, The FD subjects are categorized as lacking in the step of understanding the problem, devising a plan with deficient category, implementing the plan without looking back on the solution, so it is categorized as lacking and errors emerged at almost every step. Some errors in problem solving showed by FI and FD subjects, so for further research need to analyses errors and the other cognitive style.